CREATIVE AND INNOVATIVE TEACHER'S ATTITUDE IN DEVELOPING THE CREATIVITY OF KINDERGARTEN CHILDREN AT TK DHARMA PUTRA DENPASAR - Kadek Diah Pramanasari; Reni Anggraeni; Ida Ayu Gede Sasrani Widyastuti; Dewa Gede Satya Adi Maha Utamia (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2024)
Integrating character education into the early childhood curriculum is becoming increasingly important in the modern era, mainly to ensure the balanced development of children physically, emotionally, and intellectually. At Dharma Putra Denpasar Kindergarten, dance is used as a medium to teach character values, but the effectiveness of this approach has yet to be widely studied. This research aims to determine the efficacy of integrating character education through dance at Dharma Putra Denpasar Kindergarten in supporting holistic child development. Data was collected through direct observation, in-depth interviews with teachers, and analytical documentation related to learning plans and student projects. The validity and reliability of research results are maintained through data triangulation and member checks. The data obtained were explained inductively using open, axial, and frequency coding techniques. The research results show that using dance as a medium for character education at the Dharma Putra Denpasar Kindergarten effectively balances children's physical, emotional, and intellectual development. These findings are essential in maintaining a balance between technological progress and preserving local wisdom in education, as well as providing a reference for future curriculum development that emphasizes cultural identity and character formation from an early age.